Kepuasan Pelanggan Terhadap Loyalitas Yang Dipengaruhi Customer Experience Dan Saluran Integrasi (Omnichannel) (Studi Kasus: Bebek Pak Ndut Cabang Air Mancur Bogor) - Siti Nurhasanah; Hartanti Nugrahaningsih; Hendri Maulana (CV. ITTC INDONESIA, 2025)
The purpose of this study is to examine the influence of customer experience and channel integration (omnichannel) on customer loyalty through customer satisfaction at Bebek Pak Ndut, Air Mancur Branch, Bogor. This research employs a quantitative method, with the sample determined using the Lemeshow formula and purposive sampling technique. Data were collected through questionnaires using a Likert scale, resulting in a total sample of 97 respondents who are customers of Bebek Pak Ndut, Air Mancur Branch, Bogor. Data analysis was conducted using SmartPLS version 4.0. The results show that customer experience has a positive and significant effect on customer loyalty, with a coefficient value of 0.305, T-statistic of 2.714 (>1.96), and a P-value of 0.003 (<0.05). The Integration Channel has an insignificant effect on Customer Loyalty, with a coefficient value of 0.202, a T-statistic of 1.372 (<1.96), and a P-value of 0.085 (>0.05). Customer experience has a positive and significant effect on customer satisfaction, with a coefficient value of 0.351, T-statistic of 3.386 (>1.96), and a P-value of 0.000 (<0.05). Channel integration has a positive and significant effect on customer satisfaction, with a coefficient value of 0.509, T-statistic of 4.609 (>1.96), and a P-value of 0.000 (<0.05). Customer satisfaction has a positive and significant effect on customer loyalty, with a coefficient value of 0.338, T-statistic of 2.579 (>1.96), and a P-value of 0.005 (<0.05). Customer experience has a positive and significant indirect effect on customer loyalty through customer satisfaction, with a coefficient value of 0.119, T-statistic of 1.912 (>1.96), and a P-value of 0.028 (<0.05). Channel integration also has a positive and significant indirect effect on customer loyalty through customer satisfaction, with a coefficient value of 0.172, T-statistic of 2.310 (>1.96), and a P-value of 0.010 (<0.05).